2023
DOI: 10.3389/fvets.2023.1133605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding nano-emulsified plant oil and probiotics to drinking water during different periods besides sex on processing characteristics, physicochemical properties, and meat quality traits of broiler chickens

Abstract: IntroductionHigh-quality meat is one of the consumer demands. Therefore, several studies have concluded that supplementing broilers with natural additives can improve meat quality. This study was carried out to evaluate the effects of nano-emulsified plant oil (Magic oil®) and probiotic (Albovit®) as water additives (at the rate of 1 ml/L and 0.1 g/L, respectively) during different growing periods on processing characteristics, physicochemical properties, and meat quality traits of broilers chickens.MethodsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…These data are consistent with the findings of G.M. Suliman et al (2023), namely, the protein content increased by 0.81% (P < 0.001), the fat content decreased by 8.13% (P < 0.001). According to X.…”
Section: Discussionsupporting
confidence: 92%
“…These data are consistent with the findings of G.M. Suliman et al (2023), namely, the protein content increased by 0.81% (P < 0.001), the fat content decreased by 8.13% (P < 0.001). According to X.…”
Section: Discussionsupporting
confidence: 92%
“…The treatment diets were fixed in all experimental groups and formulated to be isocaloric and isonitrogenous to match/exceed the recommendations in the commercial sector in Saudi Arabia. A standard starter (d 0–15) and finisher (d 16–35) diets were offered in mash form based on corn-soy bean meal ( Suliman et al, 2023a ).…”
Section: Methodsmentioning
confidence: 99%
“… Abudabos et al (2021) conducted a recent study and recommended that NEVO and betaine supplements improve performance, especially at high ambient temperatures in broiler houses. In addition, Suliman et al (2023a , b ) and Al-Garadi et al (2023b) conducted a recent study and recommended that Magic oil, betaine and/or probiotics be added to the water of growing broiler programs due to favorable meat quality and the most favorable cooking loss value especially under heat stress condition. There are little or no scientific research on supplementing Magic oil with drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chronic heat stress has a negative impact on the quality of poultry meat ( 3 ). Supplementing Magic oil and probiotics is recommended for the optimal growth of broilers in poultry programs, particularly for male birds, during the period of 0 to 30 days of age ( 4 ). It has been found that supplementing male broilers with Magic oil and probiotics, especially during the first 30 days of their lives, can result in good meat chewiness due to higher springiness and lower hardness and cohesiveness.…”
Section: Introductionmentioning
confidence: 99%